Application of Integrated Marketing Approaches in Enhancing Sales in Modern Retail Businesses in Victoria Mart - Mutiara, Syadia; Daud, Daud; Fatimah, Siti; Dewi, Hasnah; Sarwono, Sarwono; Susanti, Pini; Haeran, Haeran (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to explore and analyze the marketing strategies implemented by Victorio Mart Minimarket in increasing sales and sustaining its presence amid intense market competition. The research employs a descriptive qualitative method, utilizing data collection techniques such as observation, interviews, and documentation. Informants include the business owner, employees, and consumers. The study focuses on examining the application of the 4P marketing mix (Product, Price, Place, Promotion) at Victorio Mart, while also identifying supporting and inhibiting factors, including the influence of consumer behavior trends such as FOMO (Fear of Missing Out). The findings reveal that the product strategy is primarily directed at fulfilling the community’s basic needs, accompanied by competitive and flexible pricing. The store’s strategic location serves as a major advantage. However, promotional efforts remain conventional, relying largely on banners and direct promotions. The study concludes that although Victorio Mart’s marketing strategy has been relatively effective in attracting customers and boosting sales, improvements are needed in areas such as digital marketing, inventory management, and loyalty program innovation to effectively address the competitive challenges of today’s modern retail environment.